Kredibilitas Endorser Perempuan dan Laki-laki pada Iklan Pantene Miracle Hair Supplement - Girianto, Sari Nastiti (Tuturlogi: Journal of Southeast Asian Communication, 2022)
This study aims to show that there are differences in the credibility of female and male celebrity endorsers in Pantene Miracle Hair Supplement video ads on Youtube. As well as to show that there are different responses between female and male audiences. The importance of using endorsers as communicators in advertising is because it is considered to affect the persuasion and process of communicating the information to their audiences, especially endorsers with strong credibility. In addition, the credibility of celebrity endorsers and gender endorsers is must be considered when targeting audiences with certain genders. A number of previous comparative studies compared the credibility of female and male celebrity endorsers by female and male audiences show contradict results. This study uses the source credibility model that suggest by Ohanian. This type of research is quantitative comparative with survey methods. The sampling technique uses nonprobability with quota sampling and use 125 participants. The hypothesis tested by paired and independent t-tests. This study finds results that; female celebrity endorsers are more credible than male celebrity endorsers; there is no difference in credibility for female celebrity endorsers by female and male audiences; Also, male celebrity endorsers are considered more credible by female audiences than by male audiences.